Pengaruh Literasi Finansial dan Intensitas Penggunaan Gadget Terhadap Shopping Lifestyle Mahasiswa Universitas PGRI Madiun Tahun Akademik 2019/2020 - Novita Aryani; Ruslina Yulaika; Wikanso . (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2021)
This research aimed to determine the influence of financial literacy and gadget usage intensity to shopping lifestyle of students of Universitas PGRI Madiun in academic year 2019/2020. The case of study in this research were the undergraduate students from all study programs of Universitas PGRI Madiun, with a sample size of 100 respondents who were randomly selected using Simple Random Sampling technique. This research used a quantitative approach to the type of causal associative research. The data analysis technique consisted of instrument tests which included validity and reliability tests; prerequisite test which included normality test, linearity test, multicolinearity test, and heterocedasticity test; and hypothesis test which included multiple linear regression analysis, t test, and F test. The results of the data analysis show that : (1) Financial literacy partially affects shopping lifestyle of students of Universitas PGRI Madiun, because the value of tcount > ttable (10,235 > 0,67705) and the significance value is 0,000; (2) Gadget usage intensity partially affects shopping lifestyle of students of Universitas PGRI Madiun, because the value of tcount > ttable (4,086 > 0,67705) and the significance value is 0,000; (3) Financial literacy and gadget usage intensity simultaneously affect shopping lifestyle of students of Universitas PGRI Madiun, because the value of Fcount > Ftable (546,224 > 2,70) and the significance value is 0,000.